Analgesic activity of ethanolic extract of roots of Prosopis cineraria (l.) Druce - Arvind Kumar, Sanjay Kumar Yadav, Satyawan Singh, S.N. Pandeya (Journal of Applied Pharmaceutical Science)
The present manuscript describe simple, sensitive, rapid, accurate, precise and economical Q-absorbance ratio method for the simultaneous determination of cefpodoxime proxetil and ofloxacin in combined tablet dosage form. Absorbance ratio method uses the ratio of absorbances at two selected wavelengths, one which is an isoabsorptive point and other being the ?-max of one of the two components. Cefpodoxime proxetil and ofloxacin show an isoabsorptive point at 273.2 nm in methanol. The second wavelength used is 297 nm, which is the ?-max of ofloxacin in methanol. The linearity was obtained in the concentration range of 2-14 µg/ml for both cefpodoxime proxetil and ofloxacin. The concentrations of the drugs were determined by using ratio of absorbances at isoabsorptive point and at the ?-max of ofloxacin. The method was successfully applied to pharmaceutical dosage form because no interference from the tablet excipients was found. The results of analysis have been validated statistically and by recovery studies.
Keywords: Cefpodoxime proxetil, ofloxacin, absorbance ratio method, isoabsorptive point,validation, simultaneous.